COMPARATIVE ANALYSIS OF USING GEOMETRIC TRANSFORMATION ALGORITHMS TO IMPROVE PERFORMANCE IN MOBILE APPLICATIONS - МОСИСА, А. А.; ЛАТИШЕВ, Я.-В. Г. (Technologies and Engineering, 2024)
Purpose. Scientific research in the field of mobile technologies shows that every year there is an increasing need to optimize geometric transformation algorithms to improve the performance of graphic applications. This study is dedicated to the analysis of various image transformation methods, their impact on performance, and the quality of display in mobile applications. Methodology. A comparative analysis of various geometric transformation algorithms was performed to determine the most effective ones for use in mobile graphic applications. Bilinear interpolation and affine transformations are considered as the primary methods, and the use of neural network-based methods is also evaluated. Findings. It was found that the use of optimization algorithms for geometric transformation reduces response time, effectively uses resources, improves display quality, and increases the stability and reliability of applications. Originality. A new approach to the application of neural network-based methods for geometric transformations is proposed, which allows automating the process of determining optimal transformation parameters. Practical value. The use of the proposed methods contributes to the improvement of the performance of mobile graphic applications by optimizing response time and improving image quality.